The Customizable E-cigarette Resistance Influences Toxicological Outcomes: Lung Degeneration, Inflammation, and Oxidative Stress-Induced in a Rat Model. (6th August 2019) - Cirillo, Silvia; Vivarelli, Fabio; Turrini, Eleonora; Fimognari, Carmela; Burattini, Sabrina; Falcieri, Elisabetta; Rocchi, Marco Bruno Luigi; Cardenia, Vladimiro; Rodriguez-Estrada, Maria Teresa; Paolini, Moreno; Canistro, Donatella
Abstract: Despite the knowledge gap regarding the risk-benefit ratio of the electronic cigarette (e-cig), its use has grown exponentially, even in teenagers. E-cig vapor contains carcinogenic compounds (eg, formaldehyde, acetaldehyde, and acrolein) and free radicals, especially reactive oxygen species (ROS) that cause toxicological effects, including DNA damage. The role of e-cig voltage customization on molecule generation has been reported, but the effects of the resistance on e-cig emissions and toxicity are unknown. Here, we show that the manipulation of e-cig resistance influences the carbonyls production from nonnicotine vapor and the oxidative and inflammatory status in a rat model. Fixing the voltage at the conventional 3.5 V, we observed that the amount of the selected aldehydes increased as the resistance decreased from 1.5 to 0.25 Ω. Under these conditions, we exposed Sprague Dawley rats to e-cig aerosol for 28 days, and we studied the pulmonary inflammation, oxidative stress, tissue damage, and blood homeostasis. We found a perturbation of the antioxidant and phase II enzymes, probably related to the increased ROS levels due to the enhanced xanthine oxidase and P450-linked monooxygenases. Furthermore, frames from scanning electron microscope showed a disorganization of alveolar and bronchial epithelium in 0.25 Ω group. Overall, various toxicological outcomes, widely recognized as smoke-related injuries, can potentially occur in e-cig consumers who use low-voltage and resistance device. Our study suggests that certain "tips for vaping safety" cannot be established, and encourages further independent investigations to help public health agencies in regulating the e-cig use.